Effect of rainfed and irrigated conditions on yield and quality traits of new-improved sunflower (Helianthus annuus) hybrids in a sub-humid climate - OZ, MEHMET; KARASU, ABDULLAH; KUSCU, HAYRETTIN; SINCIK, MEHMET; TURAN, Z METIN; GOKSOY, A TANJU (The Indian Journal of Agricultural Sciences, 2013)
The study was carried out to compare the effects of a rainfed (non-irrigated) and irrigated conditions on yield, certain yield components and quality traits of new-improved sunflower (Helianthus annuus L.) hybrids in southern Marmara Region, Turkey having a sub-humid climate. Over two years (2006 and 2007), significant differences for all characters except plant height and crude oil per-cent were found between irrigation regimes (irrigated and non-irrigated conditions) while genotypes showed significant differences for all characters investigated. Also, genotype × irrigation regime interaction was highly significant for all traits except crude oil percent. In addition, year × irrigation regime, year × genotype and year × genotype × irrigation regime interactions were statistically significant for head diameter, 1 000 seed weight, seed yield and crude oil yield. The seed yield and crude oil yield increased highly with irrigations. The seed yield increases for irrigated treatment compared with non-irrigated treatment were 58.3 % in 2006 and 101.4 % in 2007. Compared with non-irrigated treatment, crude oil yield increases for irrigated treatments were 56.9 % in 2006 and 99.4 % in 2007. Differences between genotypes in seed yield and crude oil yield significantly varied according to irrigated and non-irrigated conditions. The control variety, Sanay and experimental hybrid, C 10 × R 10 produced more seed yield and crude oil yield than those of others in irrigated conditions, whereas highest seed yield and crude oil yield was obtained from the control variety, Muson in non-irrigated condition and differences among other hybrids were not statistically significant under rainfed condition.